Managing the mobile workforce [ leading, building, and sustaining virtual teams - Clemons, David; Kroth, Michael S. (McGraw-Hill, 2011)
Tools and strategies for hiring, training, supporting, and motivating the more than 1 billion mobile workers worldwide